Screening of pathogenic bacteria from sea cucumber Acaudina molpadioides in Pulau Langkawi, Kedah - Li, Abigail Yen Lew; Mazlan, Nurzafirah; Anua, Siti Marwanis; Thung, Tze Young (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The outbreaks of foodborne diseases have been linked to the consumption of contaminated seafood. This research aims to screen the bacteria from the sea cucumbers Acaudina molpadioides collected from Pulau Langkawi. Methods: A total of 22 sea cucumber samples were collected randomly from Pulau Langkawi, Kedah, Malaysia. The samples were isolated and identified for the presence of bacteria using the conventional culture-based method. Presumptive bacteria colonies were subjected to various biochemical and antimicrobial susceptibility tests. Results: There were no bacterial growth in Hektoen Enteric (HE) agar and Thiosulphate-Citrate-Bile Salt (TCBS) agar. Positive samples were isolated from MacConkey (MAC) agar with 6 samples were Staphylococcus spp. (27.27%), 14 samples were Proteus spp. (63.63%) and 2 samples were Bacillus spp. (9.01%). Among these isolates, highest resistance was found against Ampicillin (45%) followed by Tetracycline (40%). Conclusion: The results indicate that the sea cucumbers Acaudina molpadioides were contaminated with potential bacteria. There is a need for adequate consumer protection measures.